Artificial Intelligence Integration in HR and Finance: A Comprehensive Framework for Strategic Transformation - Srikanth Gadde, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative role of artificial intelligence in revolutionizing human resource management and financial operations within contemporary organizations. Through a systematic analysis of current implementations and emerging technologies, the article identifies key integration pathways, critical success factors, and potential barriers to adoption across diverse industry contexts. The article synthesizes theoretical frameworks with empirical evidence to present a comprehensive understanding of how AI-driven solutions are reshaping talent acquisition, employee development, financial forecasting, and risk management functions. The article reveals significant opportunities for operational efficiency gains and strategic decision-making enhancement, while also highlighting important ethical considerations regarding algorithmic bias, data privacy, and workforce implications. The article concludes with a forward-looking assessment of future developments and provides actionable recommendations for organizations at various stages of AI maturity, contributing to both scholarly discourse and practitioner guidance in this rapidly evolving field.
Keywords: Artificial Intelligence; Human Resource Management; Financial Strategy; Predictive Analytics; Enterprise Transformation